Building Creativity Through Coding Activities of ScratchJr in Early Childhood - Hardiyanti, Widya Dwi; Prayitno, Prayitno; Pamungkas, Joko (JURNAL PENDIDIKAN USIA DINI, 2025)
Creativity is an important aspect of early childhood development, but it is often not optimal due to the limited number of interesting and effective learning media. This study aims to describe the process of digital art activities through ScratchJr to develop creativity in early childhood. This study uses a qualitative approach with a involving 13 children aged 5-6 years at IT Nur Hidayah Kindergarten Surakarta. Data was collected through documentation, observation, and interviews. Data analysis uses the qualitative descriptive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion or verification. The results of this study explain that digital art activities through ScratchJr, which uses digital technology media, can develop children's creativity through a simple coding process that is creative and fun. Children can freely express themselves with their creativity to create digital art projects through ScratchJr. Therefore, this ScratchJr media is recommended for early childhood learning to develop expression of creativity and imajination in children's art. Digital art activities are important to consider in early childhood learning, so that children can have a more optimal learning experience.